Effect of groove geometry and cutting edge in rock cutting - Doshvarpassand, S.; Richard, T.; Mostofi, Masood (Elsevier, 2017)
© 2017 Elsevier B.V. The purpose of this paper is to investigate the effects of rock/cutter interface geometry on the cutting action of a circular sharp Polycrystalline Diamond Compact (PDC) cutter tracing a groove on the surface of a rock sample. A series of laboratory cutting experiments are carried out on two sedimentary rocks (a limestone and a sandstone) using a state of the art rock scratch device. The results confirm that the magnitude of the cutting force is directly correlated to the cross-sectional area of the groove. However the results also show that the shape or geometry of the groove and in particular the length of the cutter's edge in contact with the rock, affect both the magnitude and the inclination of the force acting on the cutter. Further investigation revealed, even a sharp cutter is not perfectly sharp due to microscopic imperfections distributed along the cutters edge. Results further show that the effect of the cutter's edge can vary strongly from on rock material to another; while the effect is found negligible when carrying test in the sandstone, it is of first order in the limestone.